2020
DOI: 10.1097/gox.0000000000002383
|View full text |Cite
|
Sign up to set email alerts
|

Management of Unreconstructable Saphenous Nerve Injury with Targeted Muscle Reinnervation

Abstract: Summary: Neuroma pain significantly impacts patient quality of life and is associated with unemployment, chronic opioid dependence, and depression. Targeted muscle reinnervation (TMR), a surgical technique that coapts proximal stumps of cut nerves to distal motor nerves of adjacent muscles, has demonstrated efficacy in the treatment and prevention of neuroma pain. The objective of this study was to describe the surgical technique for TMR of the saphenous nerve, while providing a retrospective revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…This left six total studies meeting the criteria for inclusion (Figure 1 ). Two studies were low [ 3 , 18 ], three studies were moderate [ 5 , 6 , 19 ], and one study was considered at high risk of bias [ 20 ] according to the JBI assessment; additional details are available in Tables 2 , 3 .…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This left six total studies meeting the criteria for inclusion (Figure 1 ). Two studies were low [ 3 , 18 ], three studies were moderate [ 5 , 6 , 19 ], and one study was considered at high risk of bias [ 20 ] according to the JBI assessment; additional details are available in Tables 2 , 3 .…”
Section: Reviewmentioning
confidence: 99%
“…Three studies had data exclusively for primary TMR [ 3 , 5 , 6 ], one study examined only secondary TMR [ 18 ], and two studies examined both [ 19 , 20 ]. Study characteristics (including sample size, mean age, and sex) are shown in Table 4 .…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…30,48 Nevertheless, the literature is relatively sparse for this indication in both the lower and upper extremities. Specific to the lower extremity, studies are currently limited to case reports and technique articles that describe the management of sural 24 and saphenous 38 neuromas in nonamputees with limited but favorable early results. 12 A 2018 metanalysis of neuroma treatment by Poppler et al 61 did not include TMR but demonstrated a 77% overall rate of meaningful reduction in pain for prior surgical techniques such as traction neurectomy and nerve end burial.…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, it is successful in preventing recurrent stump neuroma after nonamputee symptomatic neuroma excision and has proven superior to simple neurectomy. [24][25][26][27] Recent anatomical studies have defined potential donor nerves and motor nerve targets for TMR for upper and lower extremity amputees as well as nonamputee neuromas proximal to the ankle; however, the data to support the feasibility of TMR for the management of Morton's neuroma has yet to be established. 20 Our primary goals of this investigation are to determine the consistency of the relevant anatomy in the lower extremity distal to the ankle and demonstrate the feasibility of TMR as a practical option for Morton's neuroma, particularly in the setting of recurrence.…”
Section: Introductionmentioning
confidence: 99%